Improving regional variation using quality of care measures - Scott A Berkowitz; Gary Gerstenblith; Robert Herbert; et al (Dove Medical Press, 2009)
Scott A Berkowitz1, Gary Gerstenblith1, Robert Herbert2, Gerard Anderson1,21Department of Medicine, Johns Hopkins University School of Medicine, Baltimore, MD, USA; 2Center for Hospital Finance and Management, Johns Hopkins Bloomberg School of Public Health, Baltimore, MD, USAAbstract: There is significant regional variability in the quality of care provided in the United States. This article compares regional performance for three measures that focus on transitions in care, and the care of patients with multiple conditions. Admissions for people with ambulatory care-sensitive conditions, hospital readmissions within 30 days of discharge, and compliance with practice guidelines for people with three chronic conditions (congestive heart failure, chronic obstructive pulmonary disease, and diabetes) were analyzed using data drawn from the Centers for Medicare & Medicaid Services’ Standard Analytic Files for 5% of a 2004 national sample of Medicare beneficiaries which was divided by hospital referral regions and regional performance. There were significant regional differences in performance which we hypothesize could be improved through better care coordination and system management.Keywords: performance, quality, chronic condition, ambulatory care, sensitive conditions, readmissions